2022
DOI: 10.1101/2022.10.28.22281590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The crucial role of titin in fetal development: recurrent miscarriages and bone, heart, and muscle anomalies characterize the severe end of titinopathies spectrum

Abstract: Background Titin truncating variants (TTNtv) have been associated with several forms of myopathies and/or cardiomyopathies. In homozygosity or in compound heterozygosity they cause a wide spectrum of recessive phenotypes with a congenital or childhood onset. Most recessive phenotypes showing a congenital or childhood onset have been described in subjects carrying biallelic TTNtv in specific exons. However, TTN is not yet included in many NGS panels for congenital musculoskeletal anomalies and dysmorphisms, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…analyzed clinical and molecular data from a cohort of novel and previously described recessive titinopathy cases with congenital anomalies or dysmorphisms and showed that biallelic pathogenic titin variants caused recognizable fetal and developmental defects. All newly reported patients present with a severe prenatal or congenital phenotype leading to fetal, perinatal, or infantile death, thus describe the most severe end of the titinopathies 22 . Compared with previous reports (Table 1), the clinical phenotype of rare hydrops, polyhydramnios, and paucity of fetal movements in fetus II3 in this study is indicative of a lethal recessive titinopathy 24 .…”
Section: Discussioncontrasting
confidence: 41%
“…analyzed clinical and molecular data from a cohort of novel and previously described recessive titinopathy cases with congenital anomalies or dysmorphisms and showed that biallelic pathogenic titin variants caused recognizable fetal and developmental defects. All newly reported patients present with a severe prenatal or congenital phenotype leading to fetal, perinatal, or infantile death, thus describe the most severe end of the titinopathies 22 . Compared with previous reports (Table 1), the clinical phenotype of rare hydrops, polyhydramnios, and paucity of fetal movements in fetus II3 in this study is indicative of a lethal recessive titinopathy 24 .…”
Section: Discussioncontrasting
confidence: 41%
“…Several recent reports have documented autosomal recessive congenital titinopathies associated with proteintruncating variants occurring exclusively in meta-transcript-only exons [10,[12][13][14][15][16]. Fetuses harboring metatranscript-only variants exhibit a severe phenotype characterized by developmental anomalies such as dysgenesis of the corpus callosum, congenital bone fractures, and hypoplastic heart, resulting in the highest rate of fetal lethality [17]. Homozygous recessive mutations within the Nterminal domain of the TTN gene lead to a lethal outcome and biallelic TTN variations are also associated with severe congenital titinopathy [6,15].…”
Section: Discussionmentioning
confidence: 99%